Religiosity, spirituality, and self-esteem in adolescents with cleft lip and palate: a correlational study* - Cunha, Gabriela Fávaro Marques da; Manso, Maila Meryellen Ferreira Garcia; Villela, Maria Júlia Costa de Souza; Bom, Gesiane Cristina; Mondini, Cleide Carolina da Silva Demoro; Trettene, Armando dos Santos (Revista da Escola de Enfermagem da USP, 2021)
Objective: To evaluate the correlation between religiosity, spirituality, and self-esteem in adolescents with uni- and bilateral cleft lip and palate. Method: Correlational and cross-sectional study developed in a public and tertiary hospital in Brazil between July 2018 and February 2019. The sample comprised 100 adolescents divided into two groups: G1 (unilateral cleft, 50 participants) and G2 (bilateral cleft, 50 participants). For data collection, three instruments were used: Sociodemographic Questionnaire, DUREL Religion index, Rosenberg self-esteem scale. Statistical analysis was performed with the tests Chi-squared, Mann-Whitney, Pearson Correlation, and analysis of linear correlation strength, with a 5% significance level (p ≥ 0.05). Results: Only organizational religiosity was higher in G1 when compared with G2 (p = 0.03). The overall self-esteem was satisfactory for both groups; however, there was no significant difference between them (p = 0.34). No correlation between religiosity and spirituality with self-esteem were identified for G1 and G2. Conclusion: The adolescents with uni- or bilateral cleft lip and palate presented high levels of religiosity, spirituality, and self-esteem. However, no correlation between these variables was identified.